INNOVATION MANAGEMENT AND CULTURAL TRANSFORMATION: CASE OF INDUCTIVE INITIATIVES IN BRAZILIAN SUPPORT FOUNDATION - Cintra, Leandro Pinheiro; Braga, Renato Costa; Barbosa, Allan Claudius Queiroz (Brazilian Journal of Management and Innovation (Revista Brasileira de Gestão e Inovação), 2022)
Innovations in organizations have a growing demand every year, which raises the management and encourages the process for their generation in a systematic and engaged manner. In this context, innovation appears as an organizational function in companies, which requires management of practices with ambidexterity. From this perspective, the objective of this article is to discuss the perception of employees of a Foundation for Support to Higher Education Institutions (FSHEI), with regard to initiatives to induce innovation through an institutional program of cultural transformation. We opted for a descriptive qualitative approach, integrated case study strategy. We sought to triangulate and validate data collected from different sources, related to the perception of employees; innovation acceleration agents; results of employees in the gamification of the institutional program; and internal documents on the intranet. It was possible to identify aspects related to the engagement and development of the participants; the difficulty of making work routine compatible with innovation initiatives; variations related to employee involvement and leadership support; perceptions of the importance of the program for personal and professional development; and evidence of cultural transformation towards more innovations. The results bring contributions to broaden the discussion on the innovation function, Management 3.0, the role of leaders, practices of transformation for a culture of innovation and its challenges.